MiR-1202 functions as a tumor suppressor in glioma cells by targeting Rab1A - Yu Quan; Qian Song; Jvbo Wang; Lingyu Zhao; Jian Lv; Shouping Gong (Tumor Biology)
Aberrant expression of microRNAs correlates with the development and progression of human cancers by targeting downstream proteins. MiR-1202 is downregulated in ovarian cancer and clear cell papillary renal cell carcinoma; however, its role in glioma remains unknown. The purpose of this study was to determine the expression and the role of miR-1202 and to elucidate its regulatory mechanism in glioma. We used quantitative real-time polymerase chain reaction to measure miR-1202 expression in both glioma tissues and cell lines. The findings showed that the miR-1202 expression decreased dramatically in clinical glioma tissues and cell lines, and miR-1202 expression was inversely correlated with the expression of Rab1A. Using bioinformatics and luciferase reporter assays, we identified Rab1A as a novel and direct target of miR-1202. In vitro, overexpression of miR-1202 inhibited glioma cell proliferation and induced endoplasmic reticulum stress and apoptosis through targeting Rab1A, whereas suppression of miR-1202 promoted cell proliferation and inhibited endoplasmic reticulum stress and apoptosis. Similarly, silencing Rab1A with small interfering RNA also suppressed glioma cell growth and induced endoplasmic reticulum stress and apoptosis. Taken together, our data indicate that miR-1202 suppresses proliferation and induces endoplasmic reticulum stress and apoptosis through targeting and inhibiting Rab1A in glioma cells. These results suggest miR-1202 as a potential therapeutic target for the treatment of glioma patients.